Diagnosis of tuberculosis in buffaloes in Argentina: intradermoreaction, compatible lesions and bacteriological culture - Emilia Irina Martínez; Fabiana Cipolini Galarza; Nolly María Monzón; Ana Gabriela Espasandin; José Luis Konrad; Elvira Falzoni; Soledad Barandiaran; Jimena Marfil; Marcela Martínez Vivot; Diana Elina Martínez (Revista Científica)
Bovine tuberculosis is a zoonotic disease distributed worldwide and present in Argentine herds. In Argentina, bovine and buffalo cattle are under a tuberculosis control and eradication program, which includes tuberculin purified protein derivative bovine (PPDB) diagnosis and slaughter of positive reagents. The use of this control tool is controversial in buffaloes. The aim of this study is to generate information about buffalo tuberculosis in Corrientes,Argentina, through evaluation of field diagnostic test performance, detection of tuberculosis compatible lesions in previously tuberculinized animals and, confirmation by bacteriological culture. In 8 farms, tuberculin PPDB was inoculated in the anocaudal skin fold of 566 buffaloes of 2 years old. The applied dose was 0.1ml (1mg/ml). Reading was 72 hours after inoculation with a cutimeter. Because of the lack of standardized parameters for this species, two interpretation criteria were applied, a qualitative one (reactive, when any size increase was evident in the inoculation area/non-reactive), and the quantitative one following cattle-regulated criteria (positive reaction of more than 5mm, suspicious from 3 to 5mm and negative up to 3mm). Qualitatively, 13% (73/566) reacted and 87% (493/566) did not. Quantitatively, 5% (30/566) were positive, 2% suspicious (12/566) and 93% (524/566) negative. Fifteen animals (10 reactants and 5 not reactant) were selected and followed until slaughter, where the presence of tuberculo-sis-compatible lesions was observed, and samples of lymph nodes and organs were taken for subsequent analysis by bacteriological culture and molecular typing. Of the 5 non-reactive animals, 4 of them were negative by bacteriological culture; the other buffalo turned out to be a false negative animal because it resulted positive for bacteriological culture. In 10 reacting buffaloes, 8 were confirmed positive by culture and two of them were negative. Of the 8 buffaloes with positive cultures, only 2 presented macroscopic tuberculosis-compatible lesions, one in the mediastinal lymph node and lung; and the other in the retropharyngeal ganglion. In molecular tests, the hsp65 gene was amplified to determine the genus Mycobacteria, as well as the insertion sequence IS6110, the most widely used marker for the detection of M. tuberculosis complex. According to these results, the values of sensitivity, specificity, positive and negative predictive values were 0.89; 0.67; 0.8 and 0.8, respectively. In the scenario of a previous unknown situation, this diagnostic method was used as a screening test to avoid transmission, so a highly sensitive test is needed. If the performance values continue as n increases, it could be inferred that the tuberculin test in buffaloes in the anocaudal fold would meet the premises to determine that it is a useful test for tuberculosis diagnosis.